Addictive Facebook use among Post Graduate Women Students: A Case Study of the Mangalore University, India - Krishnamurthy, M.; Veena, G. (Journal of Information and Knowledge, 2017)
This paper explains the addictive use of face book among postgraduate students of Mangalore University, India. In recent years, Social Networking Sites (SNSs) have turned into a major communication medium. The advent of social networking sites especially Face book has improved global connectivity and social interaction. The purpose of this study is to investigate of Facebook addiction among postgraduate women students. The results indicate that 37(25.69%) of respondents use Facebook to play games while 31(21.54%) to share music video, 65(45.13%) of respondents use Facebook to share information with friends, 46(31.94%) to send messages to friends, 101 (70.15%) of students are moderately addicted to using Facebook.